Polarization Correlometry of Scattering Biological Tissues and Fluids. (2020) - Bachinskyi, V. T; Wanchulyak, O. Ya; Ushenko, A. G; Ushenko, Yu. A; Dubolazov, A. V; Meglinski, Igor
No abstract available